Strategic consulting challenges and solutions for enhancing Ngo effectiveness in environmental and social responsibility - Wittmann, Sarina Raphaela (2024)
This thesis investigates the unique challenges faced by strategic consultants in supporting Non- Governmental Organizations (NGOs), with a particular focus on enhancing environmental and social responsibility. Through a case study of the Itetero Saint Hervé Community School in Rwanda, the research identifies critical barriers such as financial instability, resource constraints, and cultural differences. It proposes actionable solutions including strategic partnerships, capacity-building programs, and innovative revenue-generation methods like agrotourism. These findings aim to improve the effectiveness and sustainability of NGOs, ensuring they continue to drive meaningful social change.